Gamification and Marketing of Geotourism Destinations: Aras UNESCO Global Geopark in Iran - Sajad Ferdowsi; Sayeh Davoodi Ilkhechi (Geoconservation Research)
We explore the impact of gamification on the marketing mix of geotourism destinations. This is a form of developmental research and is descriptive-analytical in nature and method. In the first phase, data were collected to develop an initial conceptual model through a semi-structured questionnaire and expert consultations, and the results were analyzed using thematic analysis. In the second phase, the initial conceptual model was tested in the Aras Global Geopark in Iran, the case study for this research, using a structured questionnaire and structural equation modeling. We find that gamification has a positive impact on the marketing mix of Aras Global Geopark, creating a unique experience for visitors by influencing elements such as product, price, promotion, place, people, process, and physical evidence. Moreover, it enhances visitors' awareness of the significance of geoheritage, contributing to the conservation of this valuable resource.